The Image of Whiteness. - Blight, Daniel C. (Londen : Self Published Be Happy, 2019)
Broomberg and Chanarin ; Ellison, Buck ; Lewis, Nate ; Gonzalez-Day, Ken ; Thomas, Hank Willis ; Burson, Nancy ; Lucas, John ; Rankine, Claudia ; Mpagi Sepuya, Paul ; Dizon, Michelle ; Le, Viet ; Krantiz, Stacy ; Abdullah, Abdul ; Birkin, David ; Nisha Patel, Kajal ; Misrach, Richard ; Clayton, Libita ; Gabrielle, Sophie ; Madjeska, Agata ; Biswas, Sutapa ; Wolukau-Wanambwa, Stanley
The Image of Whiteness introduces readers to important extracts from the troubling story of whiteness, describing its falsehoods, its paradoxes and its oppressive nature, and highlights some of the crucial work contemporay photographic artists are doing to subvert and critique its image and its continuing power.
boek
Keywords: Daniel C. Blight